Bibliometrics of public administration research hotspots: Topic keywords, author keywords, keywords plus analysis - Wei, Ren-Zhong; Liu, Xin-Yue; Lyu, Peng-Hui (Heliyon, 2024)
This study investigates the ephemeral and common features of public administration, reviews the development of public administration, identifies current research concerns, and explores future research directions. We gathered 89,905 documents from the SSCI database from the 1920s to 2020 and used co-word analysis to assess the evolution of the discipline of public administration over the past century. The popular concerns in the field of public administration are increasingly evident, particularly as they relate to performance evaluation, sector development, governance reform, governance equity, and strategic management. The future development of public administration will likely be more closely integrated with political science, and the related research will have a stronger preference for democratization.